2015
DOI: 10.1002/pen.24098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective localization of carbon nanotubes in PA6 dispersed phase of PP/PA6 blends on the morphology evolution with time, part 1: Droplet deformation under simple shear flows

Abstract: The deformation of carbon nanotube (CNT)-filled PA6 droplets in PP matrix was examined under simple shear flows. The morphology of blends with various CNT contents in PA6 were probed by FE-SEM. Based on the wetting coefficient calculations and rheological measurements, it was noted that the majority of CNTs were selectively located in the PA6 phase for concentrations up to 2 wt%. TEM micrographs evidenced the results for a sample with 0.5 wt% CNT in PA6. Optical microscopy of the blends during simple shear flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 68 publications
(142 reference statements)
4
41
0
Order By: Relevance
“…To ascertain the possible mechanism of the morphology refinement in SEBS/TPU/OMMT nanocomposites, the location of OMMT nanoparticles has to be determined. In general, the final location of OMMT nanoparticles depends on thermodynamic and kinetics aspects, and therefore, previous studies have reported the use of classical thermodynamic methods to predict the distribution of nanoparticles in immiscible blends , and the wetting coefficient ω is defined as follows: ω=γorganoclaySEBSγorganoclayTPUγSEBSTPU where γ organoclay ‐ SEBS , γ organoclay ‐ TPU , and γ SEBS ‐ TPU are the interfacial energies between organoclay/SEBS, organoclay/TPU, and SEBS/TPU, respectively. If the calculated ω > 1, the organoclay would be preferentially located in the TPU phase; if ω < −1, the organoclay will be embedded in the SEBS phase, for −1 < ω < 1, the clays are estimated to be dispersed at the phase interface.…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain the possible mechanism of the morphology refinement in SEBS/TPU/OMMT nanocomposites, the location of OMMT nanoparticles has to be determined. In general, the final location of OMMT nanoparticles depends on thermodynamic and kinetics aspects, and therefore, previous studies have reported the use of classical thermodynamic methods to predict the distribution of nanoparticles in immiscible blends , and the wetting coefficient ω is defined as follows: ω=γorganoclaySEBSγorganoclayTPUγSEBSTPU where γ organoclay ‐ SEBS , γ organoclay ‐ TPU , and γ SEBS ‐ TPU are the interfacial energies between organoclay/SEBS, organoclay/TPU, and SEBS/TPU, respectively. If the calculated ω > 1, the organoclay would be preferentially located in the TPU phase; if ω < −1, the organoclay will be embedded in the SEBS phase, for −1 < ω < 1, the clays are estimated to be dispersed at the phase interface.…”
Section: Resultsmentioning
confidence: 99%
“…The materials and methods are fully described in the first part of this work . Here, a brief overview is provided.…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of a third component such as nanoparticles should of course affect these factors and therefore the final morphology. In the first part of this work on PP/PA6‐carbon nanotube (CNT) blends , it was evidenced by several methods that the selective localization of CNTs in the PA6 dispersed phase changed the deformability of droplets under simple shear flows. By the utilization of a shear‐optical microscope, online investigation of morphology evolutions under flow was performed with time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported the immobilization of 3‐hydroxybenzoate‐6‐hydroxylase on electrospun PCL ultrafine fibers for potential applications for heterogeneous catalysts. PA6 is a semicrystalline polymer with good tensile properties, and it has been used for textiles, adhesives, and biomedical purposes . PA6/chitosan nanofibers were used as support to immobilize Trametes versicolor laccase for the elimination of endocrine‐disrupting chemicals .…”
Section: Introductionmentioning
confidence: 99%